Transformational Leadership In The Development Of Generation Z Human Resources: Cirebon Regency Communication And Information Office - Permata, Gita Bela; Rohida, Leni (Syntax Literate, 2026)
Transformational leadership is a crucial strategic approach for promoting the growth of Generation Z human resources in public organizations, especially in addressing the complex and constantly evolving dynamics of the digital era. This study investigates transformational leadership within local government, focusing on the effectiveness of the dimensions of ideal influence, inspirational motivation, intellectual stimulation, and individual attention, as well as their impact on fostering work motivation, boosting innovation capacity, and equipping Generation Z for adaptability at the Cirebon Regency Communication and Information Agency. The research adopts a qualitative methodology, incorporating observation, interviews, and document analysis, while referencing the theories put forth by (Burns,1978) and (Bass and Avolio,1994). The results reveal that challenges in organizational culture, inadequate digital training, and ineffective mentoring systems for new employees hinder the realization of transformational leadership dimensions, particularly ideal influence, inspirational motivation, and individual attention. Although it is still evolving, transformational leadership has not yet fully facilitated the independence and creativity of Generation Z. Generation Z. The research suggests enhancing the mentoring framework, broadening digital education, and establishing environments for innovation and interdisciplinary cooperation.